Prevalence of Gastrointestinal Protozoa on Bali Cattle in Lopok Sub-District, Sumbawa District - Aldi Hamdani; Nunuk Dyah Retno Lastuti; Yeni Dhamayanti; Setiawan Koesdarto; Agus Sunarso; Poedji Hastutiek (Journal of Parasite Science (JoPS), 2021)
This study aims to determine the prevalence of gastrointestinal protozoa on Bali cattle in Lopok Sub-District, Sumbawa District. The study was conducted from January to April 2021 by taking 100 samples of Bali cattle feces from 7 villages in Lopok Sub-District, Sumbawa District. Samples were examined by sedimentation and floating methods. Species identification was determined by the morphology of the protozoa. A total of 62 (62%) samples were positively infected with protozoa. There were 4 species of gastrointestinal protozoa found infecting Bali cattle, namely Eimeria sp., Blastocytis sp., Entamoeba sp., and Balantidium sp. Most of the protozoa found in this study were Eimeria sp. (54%) and Blastocytis sp. (5%). This study found 59 samples (59%) were infected by one type of protozoa, 3 samples (3%) were infected by two types of protozoa. Cattle aged 0-6 months (81%) had a higher prevalence rate and were more susceptible to protozoal infections than cows aged 7 months – 2 years (70.3%) and more than 2 years (45.2%).